Thermal performance of vortex-based solar particle receivers for sensible heating. (1st January 2019) - Davis, Dominic; Jafarian, Mehdi; Chinnici, Alfonso; Saw, Woei L.; Nathan, Graham J.
Graphical abstract: Highlights: First order numerical heat transfer model of vortex-based solar particle receiver. Sensitivity of thermal performance to key operating parameters are assessed. Effect: gas/particle mass flow rate, flow direction, particle size, receiver length. Receiver can be configured to operate as either an air-heater or a particle-heater. Counter-flow direction relative to incident radiation tends to improve efficiency. Abstract: We report a first-order assessment of a novel vortex-based solar particle receiver and the sensitivity of its thermal performance to a number of key operational parameters. This assessment is made with a one-dimensional numerical model developed here to adapt the zonal method to calculate heat and mass transport within the enclosure of the solar vortex receiver (SVR) and to incorporate radiative and convective heat transfer between the particle phase, the air phase and the receiver wall together with re-radiative and conductive loss from the receiver. This simplified one-dimensional model allows for the systematic assessment of first order trends of mass and energy balance within the SVR and is used here to advance understanding of the dominant mechanisms controlling its thermal performance. Sensitivity studies of the thermal performance of the SVR reveal that the receiver can be configured to operate as either an air-heater or a particle-heater, depending primarily on the particle mass loading. For the present SVR configuration, the critical value of mass loading, m ̇ p / m ̇ air  ≈ 1 was found to define the boundary, above which the device acts as a particle heater, and below which it acts as an air heater. Furthermore, an assessment of the two-phase flow direction found that a counter-flow (relative to the incident concentrated solar radiation) tends to result in a higher efficiency than a co-flow direction. The first order trends of the sensitivity of thermal performance of the SVR to the particle and air mass flow rates, particle size and receiver length were also assessed, finding that the ratio of receiver thermal input to heat capacity of the two-phase flow has a controlling influence on the thermal efficiency of the SVR, particularly with the front entry configuration. Overall receiver thermal efficiencies of up to 88% were predicted for the SVR operating with high mass flow rates of both particles and air, but it is expected that the thermal efficiency of the device for all operating conditions assessed here would increase with an increase in receiver scale from the laboratory-scale device considered here.